2019
DOI: 10.6065/apem.2019.24.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Comparing adult height gain and menarcheal age between girls with central precocious puberty treated with gonadotropin-releasing hormone agonist alone and those treated with combined growth hormone therapy

Abstract: Purpose This study aimed to investigate the outcomes of gonadotropin-releasing hormone agonist (GnRHa) therapy with or without growth hormone (GH) therapy for girls with idiopathic central precocious puberty (CPP). Methods The medical records of 166 girls diagnosed with CPP from 2002 to 2017 were retrospectively reviewed. All included patients were treated with GnRHa for ≥36 months. Changes in height standard deviation score (SDS) for bone age, chronological age (CA), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Thus, an agent which can diminish the side effects of GnRHa and maintain normal growth plate development would theoretically be of great benefit for the treatment of CPP. Previous studies have reported the positive effects of GH administration on height in patients with CPP and showed that the combined use of GH and GnRHa is effective in preventing a decline in growth rate (26)(27)(28). However, GH is an expensive medicine and difficult to use in conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an agent which can diminish the side effects of GnRHa and maintain normal growth plate development would theoretically be of great benefit for the treatment of CPP. Previous studies have reported the positive effects of GH administration on height in patients with CPP and showed that the combined use of GH and GnRHa is effective in preventing a decline in growth rate (26)(27)(28). However, GH is an expensive medicine and difficult to use in conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Castro et al. report that ST has chondroprotective effects in OA ( 28 ). In the latter study, ST treatment reduced the expression of several pro-inflammatory cytokines (MMP1, IL-6, and COX-2) in both normal and inflammatory chondrocytes to prevent the degeneration of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“… 2 3 Improving the final adult height of children with CPP is one of the major issues during treatment. 5 6 However, the incidence of precocious puberty is rapidly increasing, and examination and treatment of this condition are becoming a major burden because of the associated medical expenses, although the cause of this condition remains unknown. 2 3…”
Section: Introductionmentioning
confidence: 99%
“…CPP treatment was introduced in 1980, and dosing of a recombinant GnRH agonist every 4 weeks or 3 months leads to increases in the nal adult height and delayed menarche (2,3). Improving the nal adult height of children with CPP is one of the major issues during treatment (5,6). However, the incidence of precocious puberty is rapidly increasing, and examination and treatment of this condition are becoming a major burden because of the associated medical expenses, although the cause this condition remains unknown (2,3).…”
Section: Introductionmentioning
confidence: 99%